IMPLEMENTASI STRATEGI KOMUNITAS PEMUDA HIJRAH DALAM DAKWAH DAN SYIAR ISLAM DI MEDIA SOSIAL - Irna Qurani (HIKMAH : Jurnal Dakwah dan Sosial, 2023)
The development of contemporary da'wah in Indonesia is marked by the phenomenon of the rise of hijrah communities in various cities. The Hijrah Youth Movement Community is an Islamic community that embraces all young people who have migrated in order to strengthen friendship and draw closer to Allah SWT. Pemuda Hijrah, better known as "shift" is a da'wah community that has succeeded in inviting young people in Bandung to fulfill their spiritual needs by coming to the mosque. In this study, the researcher raised a special topic regarding the concept of da'wah through social media Instagram. The qualitative research method was chosen for this research with a descriptive case study approach. Primary data collection techniques were carried out by interview and direct observation, while secondary data was obtained through literature studies conducted on various reading sources relevant to the research topic. The results showed that the da'wah communication carried out by Pemuda Hijrah among young people in the city of Bandung could change the minds of young people about the existence of a study and could also change their attitude to enthusiastically come to the Hijrah Youth study. Perkembangan dakwah kontemporer di Indonesia ditandai dengan fenomena maraknya komunitas hijrah di berbagai Kota. Komunitas Gerakan Pemuda Hijrah merupakan salah satu komunitas Islam yang merangkul seluruh pemuda yang hijrahdalam rangka untuk mempererat silaturahmi dan mendekatkan diri kepada Allah SWT. Pemuda Hijrah yang lebih dikenal dengan “shift” merupakan sebuah komunitas dakwah yang berhasil mengajak remaja Kota Bandung mengisi kebutuhan rohani dengan datang ke mesjid. Dalam penelitian ini peneliti mengangkat topik khusus mengenai konsep da’wah melalui media sosial instagram. Metode penelitian kualitatif dipilih untuk penelitian ini dengan pendekatan studi kasus deskriptif. Teknik pengumpulan data primer dilakukan dengan wawancara dan observasi langsung, sedangkan data sekunder diperoleh melaluti studi literatur yang dilakukan pada berbagai sumber bacaan yang relevan dengan topik penelitian. Hasil penelitian menunjukkan bahwa dengan komunikasi dakwah yang dilakukan Pemuda Hijrah di kalangan anak muda kota Bandung dapat mengubah pemikiran anak muda akan adanya suatu kajian dan dapat pula merubah sikap mereka untuk antusias datang kekajian Pemuda Hijrah.